Piggybacking: A successful road to the Chinese market? - Heinz Gert Preuße; Sibylle Jakubowicz (Eberhard Karls Universität Tübingen, Wirtschaftswissenschaftliche Fakultät, 1998)
The following essay deals with this kind of conflict as a possible consequence of the piggybacking strategy, presenting a theoretical part (chapter 2) followed by an empirical analysis (chapter 3). The latter is based on an opinion poll among German firms that have been asked to evaluate the relative importance of various advantages and disadvantages of international Cooperation in Chinese markets. The questionnaire was sent out in October 1997. Finally, some conclusions will be laid out.
Keywords: 330; Internationaler Markteintritt; Joint Venture; Multinationales Unternehmen; Wissenstransfer; Deutschland; China